Energy-Based Aerodynamic Analysis on the Blended-Wing-Body Aircraft with Boundary Layer Ingestion - Wenyuan Zhao; Yanlai Zhang; Jianghao Wu (International Journal of Aerospace Engineering)
This study is aimed at evaluating the energy saving benefit and its limitation of the boundary layer ingestion (BLI) applied to a transonic blended-wing-body (BWB) aircraft. The power balance method is adopted in the aerodynamic performance analysis of the aircraft. We further improve the one-dimensional analysis framework by adding the pressure volumetric work term in the power balance equation for the application in compressible flow with shock wave regions. A determining expression for the power-saving coefficient (PSC) of the BLI effect is also deduced, which is related to a BLI fraction, the airframe dissipation component ratios, and the specific thrust of the propulsor. This expression provides a way for the preliminary evaluation and comparison of BLI benefits applied in different aircraft configurations. The flow quantities of three different configurations are obtained by 3D Reynolds-averaged Navier–Stokes (RANS) numerical simulations for the calculation of aerodynamic dissipation components. The grid refinement and domain size study shows that the calculated force coefficients and total dissipation coefficient have a good convergence characteristic with the mesh refinement and are insensitive to the variation in domain size. The evaluated PSC of the BWB aircraft with a BLI propulsor is 5% using the previously developed determining expression. The maximum of PSC is 18.8%. The following comparison of dissipation components for the power-on and power-off cases shows that the benefit of BLI is slightly underestimated by the determining expression of PSC. The reason is that the variation in the boundary layer velocity profile at the trailing edge of the center body part is neglected, which is due to the installation of the propulsor. Furthermore, when the BLI propulsor is applied to a BWB aircraft, the variation in trailing edge vortex dissipation and volumetric pressure work term should be studied in detail.